O processo decisório no município de Macaé - Corrêa, Jimmy de Oliveira (2005)
This research had as objective to identify as if it gives to the process of decisions in the City of Macaé. It was a case study, therefore to make possible this analysis, the used ways had been the research of field, bibliographical and documentary. The bibliographical survey was made in books, specialized periodicals, thesis, dissertations, monographs, sites and the pertinent legislation to the case, generating an analytical base of the subject considered for study. The research also was documentary, since internal document use of the City Hall of Macaé became. In the field, the public decision-making of Macaé, the previous management, had been interviewed, so that it was understood of that it forms if gives the process of taking of decisions in this city. Moreover, the interviewed ones had been encouraged to display its beliefs and feelings, to tell to experiences and personal characteristics. With this, one searched to better understand the universe lived for the respondents and, simultaneously, to compare the speeches and the reality. The data had suffered analysis of content based on the studies from Bardin (1979), Laville and Dione (1999) and Vergara (2005). The study it approaches the City of Macaé, and, in accordance with Yin (2001), studies of cases allow to work with an immense variety of evidences, as documents, devices, interviews and comments. The research bibliographical, documentary, of field, in the case study had been complementary and with its confrontation it searched to get a general vision of form to give to reply to the final question proposal. One concludes that the process of decisions politics and its implementation in the City of Macaé if gave by means of the awareness of the executive former-managers of the City Hall, in assuming roles of true entrepreneurs, the good relationship with the Common Council, in the search of chances and the combat to the problems and the establishment of public politics, focused in the access and the improvement of the quality of the public rendering of services, in the incentive the economic development and in the promotion of the citizenship for the population place.